Holistic care for patients with severe coronavirus disease 2019: An expert consensus - Hui Wang; Tieying Zeng; Xinjuan Wu; Hong Sun (2020)
To standardize the holistic care for patients with severe coronavirus disease 2019 (COVID-19) in China.The consensus was preliminarily formed by combining relevant literature findings and frontline medical working experiences, and it was eventually confirmed by five rounds of online discussions and expert consultations.This consensus included nursing assessment, nursing priorities, nursing goals, and thirteen key points of nursing procedures such as oxygen therapy and respiratory nursing, etc.This scientific and practical consensus guideline can provide clinical guidance on the holistic nursing care of patients with severe COVID-19.